Elliptical and circular step-index fibers with conducting helical windings on the core-cladding boundaries for different winding pitch angles - A comparative modal dispersion analysis - Kumar, D.; Singh II, O.N. (My University, 2005)
The propagation characteristics of an elliptical step-index fiber with a conducting helical winding on the core-cladding boundary are investigated analytically and compared with those of a circular step index fiber with a conducting radial winding. Our optical waveguides are unconventional: in view of the existence of helical conducting windings on the core-cladding boundaries. Appropriate coordinate systems, circular cylindrical and elliptic cylindrical, are chosen for the circular and elliptical fibers. Applying the boundary conditions as modified by the presence of conducting helical windings, the characteristic equations are obtained for both the fibers. Dispersion curves are also obtained for two special values of the helical pitch angle ψ, namely, for ψ = 0° and ψ = π/2for each fiber and the results have been compared. It is found that the introduction of the helical winding has two main effects on the characteristics of both types of fibers. These are: (1) The helix introduces band gaps and (2) has the effect of splitting a mode into a pair of adjacent modes In the case of the elliptical helically clad waveguide we find two band gaps for V < 30 whereas for circular guide we have only one band gap in the same range of V -values, V being the normalized frequency parameter.
Keywords: Energy gap; Winding; Characteristic equation; Co-ordinate system; Dispersion curves; Elliptical fibers; Modal dispersion; Normalized frequencies; Propagation characteristics; Step-index fibers; Fibers